Emulating loss of coolant simulations in a pressurized heavy water reactor. (1st December 2022) - Anghel, C.V.; Deng, D.S.; Golesorkhi, S.; Shreeves, P.; Bingham, D.; Trottier, A.
Abstract: In an ideal risk-informed approach to safety analysis, all possible operational states of the system and all sources of uncertainty would be factored. Brute force approaches are cost-prohibitive if high-fidelity multiphysics simulation systems are used. To address this barrier, we present a first attempt to develop emulators for coupled neutronics/thermalhydraulics simulations of large break loss-of-coolant accidents in a generic pressurized heavy water reactor. The emulators are based on a linear mean function coupled with a locally approximate Gaussian process model. The emulators are capable of predicting the power pulse amplitude and the maximum bundle enthalpy within mean absolute relative errors of 0.75 and 0.36%, and mean relative margins of error of 1.9 and 1.0%, respectively. In relation to the simulator, the evaluation time is reduced by a factor of nearly 1800. The paper covers the simulation system, training data generation framework, statistical models and uncertainties, and results.